The Implementation of Think Pair Share Learning Model Assisted by Canva Media In Teaching Writing - Haryanti, Sri; -, Meira Regita Nurcahyani; Setyandari, Anna (Universitas Negeri Semarang, 2025)
This study aims to answer the problem “How is the implementation of think pair share learning model assisted by canva media in teaching writing of the eleventh year students of SMK Negeri 1 Klaten?”. The data used in this study are the results of the teacher and students’ interviews, questionnaires, observations, and documentations. The sources of data in this study are the teacher and the students. The writers used three steps to analyze the data, namely data analysis, data reduction, and data display. The results of the research are that the learning material used is about describing the process, the source of the material is from the handbook used by the teacher and the worksheet; and there are several steps that are taken by the teacher in carrying out the teaching and learning process by using canva learning media, namely opening, main activity, and closing. In the learning process, the teacher introduced the Think Pair Share model assisted by Canva media. Students in groups, discussed the structure and types of business letters and created their own using Canva. They shared their work with other groups and teacher, then submitted the final results to the teacher. The teacher and students showed great enthusiasm during the implementation. The implementation of the model and media increased student engagement, encouraged collaboration, and made the classroom atmosphere more active and enjoyable. It helped students better understand the material and generate ideas more easily. Thus, this model and the media can be implemented appropriately in teaching writing.